The story of Pitkis-Sport in Satakunnan kansa : content analysis of newspaper articles on a children and youth sports camp - Rantamäki, Pekko-Joonas (2014)
This study examines the media publicity of Pitkis-Sport, a children and youth sports camp, in Satakunnan Kansa, a regional newspaper. The representations of Pitkis-Sport in the paper during the camp’s 50 years of history from 1963 to 2013 will be explored by using qualitative content analysis. Furthermore, changes in the coverage between the decades will be highlighted. The study aims to find out more about how child and youth sports and physical activities are reported in Finnish regional newspapers. In addition, a quantitative table of published articles and photos is compiled and compared with the amounts of camp participants. The aim is to give insights for the future on how sport journalism should be developed in terms of covering child and youth sports.